(untitled) (Al-Academy, 2026)
there are many aspects of employing the concept of humanization with the multiplicity of analogy vocabulary that enter into the concept of humanization Contemporary international ceramic art is also replete with ceramic productions in which they embodied the concept of humanization, which is removed from stereotypes and repetition to emphasize difference and originality. One of these artists who dealt with the concept of humanization in their works was the potter (Sergei Isupov). Therefore, the researcher dealt in her current research with the topic of (humanization and its manifestations in the works of the potter Sergei Isupov). Which consisted of four chapters. In the first chapter, the methodological framework presented the research problem through the following question: What is humanization and its manifestations in the works of the potter Sergei Isupov? Then the researcher presented the importance of the research and the goal of the research, which is to identify humanization and its manifestations in the works of the potter Sergei Isupov. The researcher then identified the objective, temporal and spatial boundaries of the research. After that, the terms were defined linguistically, idiomatically and procedurally. In the second chapter, the theoretical framework, the researcher dealt with two sections: The first topic / humanization in the movement of thought and philosophy. Roots and concept. The second topic / Contemporary Russian porcelain between imitation and Westernization. In the third procedural chapter, the research community of (30) samples of the works of the potter (Sergei Ispov) was determined, (3) samples of the research sample were selected and the samples were analyzed according to the descriptive analytical method. In the fourth chapter, the researcher came out with some results and conclusions. Then the research ended by mentioning sources and references. Among the most important findings reached by the researcher are the following: 1- The Sunnah appears in the works of the sculptor Sergei Espov in forms that represent strange, intertwined, and overlapping bodies, as in samples (1) and (2). 2- Espov’s body of work is systematic, influenced by current social influences and the recurring events experienced by contemporary man.